Dementia and motor vehicle crash hospitalizations: Role of physician reporting laws. (27th February 2018) - Agimi, Yll; Albert, Steven M.; Youk, Ada O.; Documet, Patricia I.; Steiner, Claudia A.
Abstract : Objective: To determine the effect of physician reporting laws and state licensing requirements on crash hospitalizations among drivers with dementia. Methods: A study of drivers hospitalized because of vehicle crashes, identified from the State Inpatient Databases of the Agency for Healthcare Research and Quality. Multivariable logistic regression was used to examine the effect of mandatory physician reporting of at-risk drivers and state licensing requirement on the prevalence of dementia among hospitalized drivers. Results: Physician reporting laws, mandated or legally protected, were not associated with a lower likelihood of dementia among crash hospitalized drivers. Hospitalized drivers aged 60 to 69 years in states with in-person renewal laws were 37% to 38% less likely to have dementia than drivers in other states and 23% to 28% less likely in states with vision testing at in-person renewal. Road testing was associated with lower dementia prevalence among hospitalized drivers aged 80 years and older. Conclusion: Vision testing at in-person renewal and in-person renewal requirements were significantly related with a lower prevalence of dementia in hospitalized older adults among drivers aged 60 to 69 years. Road testing was significantly associated with a lower proportion of dementia among hospitalized drivers aged 80 years and older. Mandatory physician driver reporting laws lacked any independent association with prevalence of dementia among hospitalized drivers.